QT Prolongation and Associated Ventricular Tachycardia due to Cardiac Iron Load in a Patient with Thalassemia Major. (17th June 2019) - Demirtas, Derya; Demirtas, Abdullah Orhan; Sumbul, Hilmi Erdem; Koc, Ayse Selcan
Abstract : We report the case of a 23-year-old male with thalassemia major who developed long QT and continuous ventricular tachycardia (VT). Electrocardiography, echocardiography, and cardiac magnetic resonance imaging (MRI) were used for diagnosis and risk stratification. VT causes and treatments are presented and discussed. Ventricular arrhythmia can be treated by normalizing QT interval with high-dose beta-blocker therapy. However, MRI-compatible internal cardiac defibrillator implantation was performed due to the high risk in this patient.